5G will fully enable the industrial internet - Yunyong ZHANG (Dianxin kexue)
With the Ministry of Industry and Information Technology announcing that it has issued a test frequency license to China Telecom, China Mobile and China Unicom for the low and medium frequency band of the 5G mobile communication system, China's 5G commercial pace has officially begun. The global deployment, commercial situation and the oriented industrial network characteristics of 5G were introduced. It was pointed out that 5G would continue to consolidate the foundation for interconnectivity of all things, fully enable the industrial internet, and accelerate the integration of multi-industry internet.